Transgressing Gender Norms: Blurring and Transformation in Kang’s The Vegetarian - Mukhiya, Narendra Man (International Research Journal of Parroha, 2025)
This paper examines the gradual process of breaking social gender expectations and transforming into a tree-like state as a metaphor for acquiring identity as a liberated individual in Han Kang’s novel The Vegetarian. Yeong-hye, originally a dutiful wife to Mr. Cheong, begins to defy her husband and family, particularly when she refuses to eat meat and rejects physical intimacy, declaring herself to be a tree. This rebellion is interpreted by feminists as a challenge to societal conformities rooted in patriarchal psychology. Yeong-hye’s emotional and physical detachment from her husband represents a transcendence of social barriers and conformity. Drawing on the ideas of Simone de Beauvoir and Chimamanda Ngozi Adichie, the paper extends the discussion of ‘woman as other’ as a social construct, proposing that culture cannot define gender and sexuality rigidly, and individuals have the right to be unique within their families. Methodologically, the study employs textual interpretation of selected thematic lines from the primary text, connected with theoretical insights from Beauvoir and Adichie. The conclusion suggests that Yeong-hye’s plant-like state symbolizes her firm resistance to patriarchy, even at the cost of her physical well-being.